Sales management : concepts and cases - Dalrymple, Douglas J (Wiley, 1985)
Includes bibliographies and indexes.; Easily accessible, real-world and practical, Dalrymple's Sales Management 10e by Cron and DeCarlo introduces the reader to the issues, strategies and relationships that relate to the job of managing an effective sales force. With a lively and engaging style, this book places emphasis on developing a sales force program and managing strategic account relationships. With additional information on team development, diversity in the work force, problem-solving skills, and financial issues, this title provides a complete guide for taking student past the classroom and into a future career in sales management.